2018
DOI: 10.1039/c8cs00274f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the application of Diels–Alder reactions involving o-quinodimethanes, aza-o-quinone methides and o-quinone methides in natural product total synthesis

Abstract: In recent decades, transient and highly reactive ortho-quinodimethanes (o-QDMs), ortho-quinone methides (o-QMs) and aza-ortho-quinone methides (aza-o-QMs) have attracted much attention and have been extensively studied and applied in organic synthesis, especially natural product total synthesis. This review summarizes recent advances in Diels-Alder reactions involving in situ-generated o-QDMs, o-QMs and aza-o-QMs, highlighting the power and potential of this strategy in organic synthesis and natural product to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(154 citation statements)
references
References 360 publications
1
144
1
2
Order By: Relevance
“…Twoc hiral aliphatic sulfonic acids, (À)-CSA (entry 3) and (+)-CSA (entry 4), were further evaluated, and there is no chiral recognition observed fort he formation of the product 4aa with up to 32 % ee albeit in a slightly increased yield of 70 %. In addition to the above Brønsted acids, two Lewis acids, Zn(OTf) 2 and Sc(OTf) 3 ,w ere also employed in ac atalytic fashion. Compared with the negative result when using Sc(OTf) 3 (entry 6), less acidic Zn(OTf) 2 delivered 4aa in 56 %y ield with an increased ee value of 66 % (entry 5), in which the acetal intermediate 5aa (a/b = 1.7:1) resulting from the tandemr earrangementw as isolated in 39 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twoc hiral aliphatic sulfonic acids, (À)-CSA (entry 3) and (+)-CSA (entry 4), were further evaluated, and there is no chiral recognition observed fort he formation of the product 4aa with up to 32 % ee albeit in a slightly increased yield of 70 %. In addition to the above Brønsted acids, two Lewis acids, Zn(OTf) 2 and Sc(OTf) 3 ,w ere also employed in ac atalytic fashion. Compared with the negative result when using Sc(OTf) 3 (entry 6), less acidic Zn(OTf) 2 delivered 4aa in 56 %y ield with an increased ee value of 66 % (entry 5), in which the acetal intermediate 5aa (a/b = 1.7:1) resulting from the tandemr earrangementw as isolated in 39 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Importantly,t he transient o-QM entitiesg enerated in situ are widely harnessed in many chemical, medicinal, and biologic processes such as enzymei nhibition, DNA alkylation, and lignin oligomerization, showingt he general existence and importance of o-QMs in nature. [2] Owing to its intrinsic electrophilicity,a ttributed to the zwitterionic characteristic andt he aromatization drivingf orce, o-QMs as a class of quinoids have been extensively utilized for multiple decades in organic synthesis, wherein the design and development of new and novel methodologies of o-QMs have received significant attention in the field of asymmetric catalysis. [3] Amongs uch efforts, the aromatization-driven reaction modes including 1,4-addition (route a, Scheme 1) [4] and [4 + n]a nnulation (n = 1, 2, and3 ;r oute b, Scheme 1) [5][6][7] have been previ-ously pioneered in asymmetricc atalysis and synthesis, providing powerful tools for access to synthetically useful aromatic buildingb locks.…”
mentioning
confidence: 99%
“…And, the best photo reaction condition is photolysis of a solution of 10 (0.01mol/L) in dichloroethane under UV light (λ max = 366 nm) in the presence of Ti(Oi-Pr) 4 (3.0 equiv. ), which gave the desired cycloadduct in 62% isolated yield and good diastereoselectivity (dr = 11 : 1) ( Based on the structure of the photo-adducts and the previous intermolecular PEDA reaction studies, [8] we proposed the process of the photo reaction (Scheme 2). The photo-induced enolization of 10 will first generate the hydroxy-o-quinodimethane intermediate, which bears disubstituted groups on the benzylic position and belongs to the stereo-hindered diene species.…”
Section: Resultsmentioning
confidence: 99%
“…This method allows stereospe-cific formation of core structures of aromatic abietane diterpenoids and sesquiterpenoids, which was successfully used in the synthesis of indolosesquiterpenoid mycoleptodiscin A. Recently, we systematically studied the intermoleculer PEDA reaction, [8] which was first discovered by Yang in 1961. [9] We found that Lewis acid [Ti(Oi-Pr) 4 ] plays a key role in this photolysis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Aza-o-quinone methide (1) and its analogues are important and unstable intermediates. [6][7][8][9][10][11][12][13][14][15][16][17] They may carry out [4 + 1], [6][7][8] [4 + 2] [9][10][11][12][13] and [4 + 3] [14] cycloadditions to form tetrahydroquinolines, [9,[11][12][13] quinolines, [9,10] indoles [6][7][8] and benzotriazepine, [14] which are useful scaffolds to build many drugs and natural products, [9] such as virantmycin, [15] and chartellin. [16] Interestingly, to carry out the cycloaddition reactions, in-situ generated 1 needs to be in alkaline conditions, instead of acidic conditions.…”
Section: Introductionmentioning
confidence: 99%